Rapid start antiretroviral therapies for improved engagement in HIV care: implementation science evaluation protocol - Beth Bourdeau; Starley B. Shade; Kimberly A. Koester; Greg M. Rebchook; Wayne T. Steward; Bruce M. Agins; Janet J. Myers; Son H. Phan; Marlene Matosky (BMC, 2023)
Abstract Background In 2020, the Health Resources and Services Administration's HIV/AIDS Bureau funded an initiative to promote implementation of rapid antiretroviral therapy initiation in 14 HIV treatment settings across the U.S. The goal of this initiative is to accelerate uptake of this evidence-based strategy and provide an implementation blueprint for other HIV care settings to reduce the time from HIV diagnosis to entry into care, for re-engagement in care for those out of care, initiation of treatment, and viral suppression. As part of the effort, an evaluation and technical assistance provider (ETAP) was funded to study implementation of the model in the 14 implementation sites. Method The ETAP has used implementation science methods framed by the Dynamic Capabilities Model integrated with the Conceptual Model of Implementation Research to develop a Hybrid Type II, multi-site mixed-methods evaluation, described in this paper. The results of the evaluation will describe strategies associated with uptake, implementation outcomes, and HIV-related health outcomes for patients. Discussion This approach will allow us to understand in detail the processes that sites to implement and integrate rapid initiation of antiretroviral therapy as standard of care as a means of achieving equity in HIV care.